THE RHEOLOGY OF SUSPENSIONS BASED ON ORGANIC SUBSTANCES (ON THE EXAMPLE OF CELLULOSE) - Genjemuratova , G.P.; Shambilova , G.K.; Kabiden , K.K. (Eurasian Journal of Academic Research, 2024)
In this article, we will explore the rheology of suspensions based on organic substances, focusing on cellulose as a case study. We will examine the properties of cellulose suspensions, factors affecting their rheology, characterization techniques, and their applications in various industries. By understanding the rheological behavior of cellulose suspensions, we can optimize their performance and enhance their usability in different applications.